I have x/4 = lny This simplifies to y=e^(x-4)
Can someone help me understand the basic inverse properties of ln and e that would make x/(4 x ln)=y simplify to the answer above? Thanks.
I'm not sure "simplify" is the right word.
You should have this property...The following Two statements are identical.
1) $\displaystyle log_{b}(a) = c$
2) $\displaystyle b^{c} = a$
For suitable a, b, and c.
How does this apply to your problem statement?
Revise: See, SIRON even called it a "Definition". It's not really a "simplify" thing.